2014
DOI: 10.1186/s13068-014-0162-2
|View full text |Cite
|
Sign up to set email alerts
|

Insights into high-efficiency lignocellulolytic enzyme production by Penicillium oxalicum GZ-2 induced by a complex substrate

Abstract: BackgroundAgricultural residue is more efficient than purified cellulose at inducing lignocellulolytic enzyme production in Penicillium oxalicum GZ-2, but in Trichoderma reesei RUT-C30, cellulose induces a more efficient response. To understand the reasons, we designed an artificially simulated plant biomass (cellulose plus xylan) to study the roles and relationships of each component in the production of lignocellulolytic enzymes by P. oxalicum GZ-2.ResultsThe changes in lignocellulolytic enzyme activity, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 64 publications
2
24
0
1
Order By: Relevance
“…In particular, the genera Aspergillus and Penicillium were abundant (12.46% and 10.72%, respectively). It is well known that anaerobic fungi of these two genera produce cellulolytic and hemicellulolytic enzymes for cellulosic biomass degradation (Boots et al, ; Mortensen et al, ; Solomon, Haitjema, & Henske, ; Liao, Li, Wei, Shen, & Xu, ; Tani, Kawaguchi, & Kobayashi, ). Similarly, recent evidence indicates that species of the genus Fusarium are robust cellulose and hemicellulose degraders (Huang, Busk, & Lange, ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the genera Aspergillus and Penicillium were abundant (12.46% and 10.72%, respectively). It is well known that anaerobic fungi of these two genera produce cellulolytic and hemicellulolytic enzymes for cellulosic biomass degradation (Boots et al, ; Mortensen et al, ; Solomon, Haitjema, & Henske, ; Liao, Li, Wei, Shen, & Xu, ; Tani, Kawaguchi, & Kobayashi, ). Similarly, recent evidence indicates that species of the genus Fusarium are robust cellulose and hemicellulose degraders (Huang, Busk, & Lange, ).…”
Section: Discussionmentioning
confidence: 99%
“…The two most dominant genera, were Aspergillus (12.46%) and Penicillium (10.72%). It has been reported that the anaerobic species of these two genera can produce cellulolytic and hemicellulolytic enzymes, which are beneficial to cellulosic biomass degradation (Boots et al 2013;Liao et al 2014;Shuji et al 2014;Solomon et al 2016;Trinci et al 1994). Similarly, as robust cellulose and hemicellulose degrader, the genus Fusarium was reported in a recent study (Huang et al 2015).…”
Section: Gut Fungal Microbiome and Feeding Ecology Of Tibetan Macaquesmentioning
confidence: 95%
“…Singhania et al (2014) demonstrated that P. janthinellum EMS-UV-8 is a fungus with potential for future largescale production of cellulase. Liao (2014) reported induced high-efficiency lignocellulolytic enzyme production by Penicillium oxalicum on complex substrates. Moubasher and Mazen (1991) isolated some fungal species from Egyptian soils and assayed their cellulolytic activities.…”
Section: Lignocellulolytic Activity Of Selected Isolates In Solid Stamentioning
confidence: 99%